Revitalizing MSMEs in the Digital Age: Strengthening Brand Identity and Digital Payment Ecosystem at Siomay Batagor Tirtayasa Business - Annisa, Eva; Merlyana, Anggun; Alfattah, Dhiwa Abiyu; Gea, Iman Jaya; Putri, Resha Moniyana; Darmawan, Arif (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as vital contributors to national economic growth, especially in terms of employment creation and community empowerment. Despite this potential, many MSMEs continue to face barriers in brand development, digital marketing, and the adoption of modern financial technologies. This community service program was designed to provide practical solutions for the Siomay Batagor Tirtayasa MSMEs in Sukabumi, Bandar Lampung City, focusing on three main strategies: enhancing brand visibility through promotional banner design, implementing QRIS-based digital payment systems, and providing digital marketing training via social media. As a result, the business experienced increased visibility, marked by a significant rise in new customers just two days after the banner installation, indicating the strong influence of professional branding. The implementation of QRIS also made the transaction process smoother, with 30% of transactions in the first week conducted digitally, reflecting improved customer convenience and trust. Positive customer responses further supported the impact of these changes, especially among younger consumers who preferred cashless payments and easily accessible product information. The business owner also showed increased awareness and confidence in managing digital tools independently. This program demonstrates that even simple and participatory interventions can significantly enhance MSMEs competitiveness in the digital age. For further research, this approach can be developed through deeper digital literacy training, integration into marketplace platforms, or partnerships with local government to scale up the impact on other MSMEs.